Criteria for government spending : a report of the Economic Advisory Council - Chamber of Commerce of the United States of America (Washington : Chamber of Commerce of the United States, 1962)
This report focused on the economy and efficiency are relevant objectives in any activity, but naturally those government activities which use up the most resources deserve the most attention.
Includes bibliography.
osa 11/4/19
Keywords: Fiscal policy; Government spending; Budget